Synthesis and Biological Activities of Oxovanadium(IV) Complexes of Schiff Bases - Ahmad Khan, Shuyeb; Kumar, Mohit (Asian Journal of Chemistry, 2010)
Schiff bases like N-benzoyl-1-N-2-furan thiocarbohydrazone (A), thiophine-2-aldehyde ophenylene diamine (B) and thiophene 2-aldehyde m-phenylene diamine are formed by the condensation of different carbonyl and amino compounds. The oxovanadium(IV) complexes of these Schiff bases have been characterized on the basis of elemental analysis, molar conductance, magnetic susceptibility, electronic, IR and ESR spectra.